PENGEMBANGAN WEBSITE FAKULTAS TEKNIK MENGGUNAKAN FRAMEWORK CODEIGNITER VERSI 3 DENGAN METODE AGILE - Dhea Adira Titania; ANGGA RIYANDI SAPUTRA (Yayasan Nuraini Ibrahim Mandiri, 2024)
The Center for Information Systems and Networks at Universitas PGRI Madiun is responsible for maintaining and developing network infrastructure and information systems. This research aims to overcome the weaknesses of the Faculty of Engineering website which requires editing the program code when menus are added and adding a filter feature to the achievements menu to make it easier for the faculty to create reports. The agile method was chosen for development because the agile method is flexible to change. Its ability to respond to changing needs quickly, while CodeIgniter was chosen to be able to help develop websites quickly. The research results show an increase in website function with ease of menu settings and the addition of filter features in the achievements menu, although with black box testing there are still discrepancies in the features of news visitor traffic, announcement visitor traffic, and agenda visitor traffic.